1999
DOI: 10.1177/003435529904300103
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Agency Leadership Style

Abstract: One hundred five rehabilitation employees were surveyed on the effect of leadership style on subordinates' perceptions of their work environment and on their job satisfaction. Findings suggest that leadership style affects service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A research conducted by Packard & Kauppi (1999) found that employees with supervisors having democratic management styles experienced higher level of satisfaction than with autocratic leadership style. Bassett (1994) maintains that supervisors bringing the humanistic part to the job and contribute towards increasing the employee's level of job satisfaction.…”
Section: Supervision and Job Satisfactionmentioning
confidence: 99%
“…A research conducted by Packard & Kauppi (1999) found that employees with supervisors having democratic management styles experienced higher level of satisfaction than with autocratic leadership style. Bassett (1994) maintains that supervisors bringing the humanistic part to the job and contribute towards increasing the employee's level of job satisfaction.…”
Section: Supervision and Job Satisfactionmentioning
confidence: 99%
“…Several studies have also suggested that the personal style of leaders may negatively influence the working climate and the productivity of the organization (Ekvall et al , 2002; Kets de Vries and Miller, 1984). While supportive leaders seem to increase the subordinates' job satisfaction (Packard and Kauppi, 1999), by contrast subordinates who perceived themselves to be bullied by their leaders experience low job satisfaction and report many symptoms of health problems (Skogstad, 1997). It is therefore not surprising that stress research has revealed that abusive and tyrannical leaders are an important source of stress for subordinates (Hogan, 1994; Hogan and Hogan, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Ali and Akhter (2009), Kyamanywa (1996), andVenter (1998) showed that leadership style significantly affected job satisfaction of academic members in higher education institution. A research conducted by Packard & Kauppi (1999) found that employees with supervisors having democratic management styles experienced higher level of satisfaction than with autocratic leadership style. Furthermore, the important role management can play in the job satisfaction of academics.…”
Section: The Regression Between Faculty Job Satisfaction and Demograpmentioning
confidence: 99%